The PRISMA-LHAASO project: Status and overview - Alekseenko Victor; Bagrova Anastasia; Cui Shuwang; He Yayun; Li Bingbing; Ma Xinhua; Pozdnyakov Egor; Shchegolev Oleg; Stenkin Yuri; Stepanov Vladimir (EPJ Web of Conferences, 2017)
The status of and main features of the PRISMA-LHAASO project are presented. We discuss here the science project and some preliminary results obtained with the PRISMA prototype.